(untitled) (Bangladesh Journal of Infectious Diseases, 2023)
Background: Wound infection gaining utmost importance day by day because of emergence of drug resistant bacteria. Objective: This study was carried out to see the pattern of aerobic bacterial pathogens along with MRSA and ESBL producing strains causing wound infection. Methodology: This cross sectional study was conducted from May 2010 to April 2011. Wound swabs were taken from the patients suffering from wound infections admitted in the different surgical wards of Rajshahi Medical College Hospital, Rajshahi, Bangladesh. The study place was the department of Microbiology of Rajshahi Medical College, Rajshahi and department of General Surgery, Orthopedic Surgery and Gynaecology & Obstetrics of Rajshahi Medical College Hospital, Rajshahi. Two wound samples were collected from each patient with, one for microscopy and other for culture. Gram staining and culture of collected wound swab were done for isolation and identification of MRSA and ESBL Bacteria. Antimicrobial susceptibility testing of the isolates were performed by using modified Kirby-Bauer technique using Mueller-Hinton agar and commercially available antimicrobial discs manufactured by Oxoid Diagnostic. Results: A total of 300 samples were collected. Culture yielded growth of 175(58.33%) cases, of which 138 (78.86%) were gram negative. From total 138 of gram negative bacteria 52(37.68%) were ESBL positive and they were distributed as K. pneumoniae 05(55.56%), E. coli 35(54.68%), Pr. mirabilis 05(20.83%) and Ps. aeruginosa 05(17.00%). All the ESBL producers were 100.0% resistant against ampicillin, cotrimoxazole, ceftriaxone and ceftazidime. Ciprofloxacin was 80.0 to 88.6%, gentamicin was 40.0 to 60.0%, aztreonam was 60.0 to 100.0% and netilmycin was 20.0 to 60% resistant. All the MRSA were 100.0% resistant against ampicillin, co-trimoxazole and cloxacillin. None showed resistance against vancomycin. Conclusion: Drug resistant ESBL producing bacteria and MRSA are quite high among the isolated pathogens with resistant to most of the antimicrobial agent. Bangladesh Journal of Infectious Diseases, June 2022;9(1):15-24